Transduction of Herpesvirus saimiri-Transformed T Cells with Exogenous Genes of Interest - Martínez-Barricarte, Rubén; De Jong, Sarah Jill; Markle, Janet; De Paus, Roel; Boisson-Dupuis, Stephanie; Bustamante, Jacinta; Van de Vosse, Esther; Fleckenstein, Bernhard; Casanova, Jean Laurent (Current Protocols in Immunology, 2016)
Human T cells can be transformed and expanded with herpesvirus saimiri (HVS). HVS-transformed T cells from patients have facilitated the study of a broad range of primary immunodeficiencies (PID) in which T-cell development or function is altered. However, the utility of HVS-transformed T cells for genetic studies has been limited by technical challenges in the expression of exogenous genes, including wild-type or mutant alleles. A novel, gamma retrovirus-based method for the simple and reliable transduction, purification, and study of HVS-transformed T cells is described. © 2016 by John Wiley & Sons, Inc.
EVALuna2:35292